PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP MOTIVASI BELAJAR IPAS SISWA KELAS IV UPTD SD NEGERI 55 PAREPARE - Ila Israwaty; Usman; Amnah Maharani Sakaria (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the influence of the application of the Problem Based Learning (PBL) learning model on the motivation to learn science in grade IV at UPTD SD Negeri 55 Parepare. The background of this research is based on low motivation to learn. This study uses a quantitative approach, a type of experimental research with the type of Nonequivaent Control Group Design. The population of this study includes all students in the school with a total of 280, with the research sample consisting of 40 of which 21 students of class IV.A as the control class and 19 students of class IV.B as the experimental class. Data was obtained using questionnaires given during the pretest (initial test) and posttest (final test). The data was analyzed using the Independent Sample T-Test statistical test. The results of the statistical test showed that Sig (2-tailed) = 0.000. This indicates that the significance value is less than 0.05. (0.000 < 0.05), so that H0 is subtracted and is accepted. In addition, the results of descriptive statistical analysis also showed that the average score of the experimental class was higher, which was 80.68 compared to the control class with a score of 66.67. This indicates that classes that apply the Problem Based Learning (PBL) learning model have an effect on the motivation of learning science students in grade IV of UPTD Negeri 55 Parepare.